Equipment-free recombinase polymerase amplification assay using body heat for visual and rapid point-of-need detection of canine parvovirus 2. (June 2018) - Liu, Libing; Wang, Jianchang; Geng, Yunyun; Wang, Jinfeng; Li, Ruiwen; Shi, Ruihan; Yuan, Wanzhe
Abstract: A visible and equipment-free recombinase polymerase amplification assay combined with a lateral flow strip (LFS RPA) was developed to detect canine parvovirus type 2 (CPV-2), which is the etiological agent of canine parvovirus disease. The CPV-2 LFS RPA assay was developed based on the VP2 gene and is performed in a closed fist using body heat for 15 min; the products are visible to the naked eye on the LFS within 5 min. The assay could detect CPV-2a, CPV-2b and CPV-2c, and there was no cross-reaction with the other viruses tested. Using the standard CPV-2 DNA as a template, the analytical sensitivity was 1.0 × 10 2 copies per reaction, which was the same result as that of a real-time PCR. The assay performance was further evaluated by testing 60 canine fecal samples, and CPV-2 DNA was detected in 46 samples (76.7%, 46/60) by LFS RPA, which was the same result as that of the real-time PCR assay and higher than that of the SNAP method (48.3%, 29/60). The novel CPV-2 LFS RPA assay is an attractive and promising tool for rapid and convenient diagnosis of CPV disease, especially cage side and in underequipped laboratories. Highlights: Visual and rapid molecular assay for detection of CPV-2 was developed. Assay was based on recombinase polymerase amplification and use of lateral flow strip to visualize product. Assay was incubated successfully in a closed fist using body heat. Assay showed high sensitivity and specificity for detection of CPV-2.